After Zagora — Andrian Colonization in the Northern Aegean: The Case of Argilos - Perreault, Jacques Y.; Bonias, Zisis (Mediterranean Archaeology: The Australian and New Zealand Journal for the Archaeology of the Mediterranean World, 2012)
For the last twenty years, a team of Greek and Canadian archaeologists have been excavating Argilos, the earliest known Greek colony in the area of the mouth of the Strymon river. An overview of research on what was one of the four colonies founded by Andrians after the abandonment of Zagora allows discussion of questions related to the origin of the settlers, the choice of location, the foundation date, and the reasons for the settlement. First occupied by Thracians, Argilos was settled by Greeks no later than the mid-7th cent. B. C. Some of these Greeks came from Andros ; however, one should not eliminate the possibility that Argilos may have been a joint venture between Andrians and Chalcidians. Cohabitation between Greeks and Thracians lasted until the mid-6th cent., when it is believed a wave of immigrants arrived, some of whom were from east Greece. Argilos remained affluent until the foundation of Amphipolis in 437, after which it suffered decline. Its capture by Philip II in 357 and the deportation of its inhabitants to Amphipolis put an end to its existence.

Argilos, 25 années de recherches : organisation de la ville et de la campagne dans les colonies du nord de l’Égée, VIIIe - IIIe siècles av. n. è. : actes du colloque de Thessalonique, 25-27 mai 2017 - Bonias, Zisis; Perreault, Jacques Y. (Publications of the Canadian Institute in Greece = Publications de l’Institut Canadien en Grèce, 2021)

3. Argilos aux VIIe - VIe siècles - Perreault, Jacques-Yves; Bonias, Zisis (Grecs et indigènes de la Catalogne à la mer Noire : Actes des rencontres du programme européen Ramses2 (2006-2008), 2010)
This article deals with the Greek colonization of ancient Argilos which took place towards the middle of the 7th century B.C., and addresses the question of cohabitation between the Greek colonists and the native Thracian population. A study of the archaeological remains, the literary sources and the development of Greek penetration in the lower region of the Strymon river tends to show that Greeks and Thracians did live together in Argilos, but also in several other sites of this region.
Keywords: Thraces; colonisation grecque

Isotopic evidence for animal management strategies at Archaic and Classical period Argilos, Greece - Alagich, Rudolph; Gkotsinas, Angelos; Perreault, Jacques Y.; Bonias, Zisis; Smith, Colin (Journal of Archaeological Science: Reports, 2022)
This paper utilizes the stable carbon and nitrogen isotopic composition of bulk animal bone collagen to better understand animal management practices in Archaic and Classical period Argilos in northern Greece. The results from Argilos are compared with data from other sites in northern Greece to provide new insights into herd management in the region over time. Our results reveal some changes in cattle and pig diets at Argilos between the Archaic and Classical periods. Throughout both periods cattle and caprines exhibit evidence of having consumed C4 vegetation, likely obtained from the nearby salt marshes in the Strymon river delta. This dietary regime is similar to that observed at other north Aegean sites dating back to the Neolithic, suggesting that the long tradition of animal herding in the marshes was an environmentally specific practice in the region.
Keywords: Agriculture; Argilos; Classical period; Greece; Stable isotopes

L' habitat d'Argilos: les céramiques archaïques, un aperçu - Perreault, Jacques Y.; Bonias, Zisis I. (Les clients de la céramique grecque: actes du colloque de l'Académie des inscriptions et belles-lettres, Paris, 30-31 janvier 2004, 2006)
Description de la céramique par phases chronologiques entre 650 et 500 av. J.-C.

Argilos: the booming economy of a silent city - Perreault, Jacques Y.; Bonias, Zisis (Making cities: Economies of production and urbanization in Mediterranean Europe, 1000–500 BC, 2021)

The Fieldwork of the Canadian Institute in Greece, 2011 - Rupp, David W.; Aravantinos, Vassilis; Burke, Brendan; Burns, Bryan; Begg, Ian; Nelson, Michael; Brenningmeyer, Todd; Kelly, Amanda; Bonias, Zisis; Perreault, Jacques; Karapanou, Sophia; Haagsma, Margriet (Mouseion: Journal of the Classical Association of Canada, 2012)
The archaeological fieldwork conducted in Greece in 2011 under the aegis of the Canadian Institute in Greece (CIG) is summarized based on the presentation given by the director at the institute’s annual Open Meeting in Athens in May 2012. , Les travaux archéologiques menés en Grèce en 2011 sous l’égide de l’Institut canadien en Grèce sont présenté sur la base d’une allocution donnée par le directeur lors de l’assemblée publique annuelle à Athènes en mai 2012.

The Fieldwork of the Canadian Institute in Greece, 2010 - Rupp, David W.; Bonias, Zisis; Perreault, Jacques Y.; Karapanou, Sophia; Haagsma, Margriet J.; Begg, D. J. Ian; Nelson, Michael C.; Aravantinos, Vassilis; Burke, Brendan; Burns, Bryan; Tankosic, Zarko; Keller, Donald R. (Mouseion: Journal of the Classical Association of Canada, 2012)
The archaeological fieldwork conducted in Greece in 2010 under of aegis of the Canadian Institute in Greece is summarized on the basis of a presentation given by the director at the institute’s annual Open Meeting in Athens, in May 2011. These research activities included excavations (Argilos and Kastro Kallithea), a pedestrian survey (Karpathos), and study seasons (Eastern Boeotia and Southern Euboea). , Les travaux archéologiques menés en Grèce en 2010 sous l’égide de l’Institut canadien en Grèce sont passés en revue dans le cadre d’une présentation donnée par le directeur lors de l’Assemblée publique annuelle, tenue à Athènes en mai 2011. Ces recherches comptaient des fouilles (Argilos et Kastro Kallithéa), une prospection (Karpathos) et des campagnes d’étude (Boétie orientale et Eubée sud).

Fieldwork of the Canadian Institute in Greece in 2018 - Burke, Brendan; Athanasoulis, Dimitris; Bonias, Zisis; Burns, Bryan; Carter, Tristan; Charami, Alexandra; Gallimore, Scott; Haagsma, Margriet J.; James, Sarah; Karapanou, Sophia; Nakassis, Dimitri; Papadimitriou, Alcestis; et al. (Mouseion: Journal of the Classical Association of Canada, 2021)
The archaeological fieldwork conducted in Greece in 2018 under the aegis of the Canadian Institute in Greece (CIG) is summarized based on the presentation given by the director at the Institute’s annual Open Meeting in Athens in May 2019.